Non-covalent acetylcholinesterase inhibitors: In vitro screening and molecular modeling for novel selective insecticides. (December 2022) - Hepnarova, Vendula; Hrabinova, Martina; Muckova, Lubica; Kucera, Tomas; Schmidt, Monika; Dolezal, Rafael; Gorecki, Lukas; Hrabcova, Veronika; Korabecny, Jan; Mezeiova, Eva; Jun, Daniel; Pejchal, Jaroslav
Abstract: Insecticides represent the most crucial element in the integrated management approach to malaria and other vector-borne diseases. The evolution of insect resistance to long-used substances and the toxicity of organophosphates (OPs) and carbamates are the main factors contributing to the development of new, environmentally safe pesticides. In our work, fourteen compounds of 7-methoxytacrine-tacrine heterodimers were tested for their insecticidal effect. Compounds were evaluated in vitro on insect acetylcholinesterase from Anopheles gambiae ( Ag AChE) and Musca domestica ( Md AChE). The evaluation was executed in parallel with testing on human erythrocyte acetylcholinesterase ( Hss AChE) and human butyrylcholinesterase ( Hss BChE) using a modified Ellman's method. Compound efficacy was determined as IC50 values for the respective enzymes and selectivity indexes were expressed to compare the interspecies selectivity. Docking studies were performed to predict the binding modes of selected compounds. K1328 and K1329 provided high Hss AChE/ Ag AChE selectivity outperforming standard pesticides (carbofuran and bendiocarb), and thus can be considered as suitable lead structure for novel anticholinesterase insecticides. Graphical abstract: Unlabelled Image Highlights: Acetylcholinesterase inhibitors represent the crucial approach in malaria treatment. Inhibition of Ag AChE, Md AChE, Hss AChE and Hss BChE was establish. IC50 values of 7-methoxytacrine-tacrine heterodimers were compared to standard. K1328 and K1329 are suitable structure for novel insecticides thanks to high selectivity.